1987
DOI: 10.1080/00480169.1987.35429
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic non-progressive pneumonia on weight gain of pasturefed lambs

Abstract: The liveweight gains and carcass weights of 40 lambs grazed under pastoral conditions were compared with those of a similar group with chronic non-progressive pneumonia which had been induced by intranasal inoculation of an aerosol of homogenised pneumonic lung at about 120 days of age. Half the lambs from each group were killed 30 days post-inoculation following rotational grazing on high quality pasture. At this time the pneumonic lambs had a mean liveweight gain of 1.74 kg less than the controls. The remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…Interestingly, the most pronounced group-associated differences in average daily gains occurred during the first month on feed, when average daily gains were 0.26 ± 0.16 (mean ± SD) for exposed lambs and 0.039 ± 0.13 for unexposed lambs ( P =0.008, 2-sample t-test), coinciding with the period when the prevalence of M. ovipneumoniae infection increased from 33% to 100% of the exposed lamb group. Others have also observed that the most dramatic effects of experimentally reproduced chronic non-progressive pneumonia occur during the first 30 days after challenge [5, 6]. Analysis of variance was conducted using the model ADG ~ Group + Sex + Birth type + error.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the most pronounced group-associated differences in average daily gains occurred during the first month on feed, when average daily gains were 0.26 ± 0.16 (mean ± SD) for exposed lambs and 0.039 ± 0.13 for unexposed lambs ( P =0.008, 2-sample t-test), coinciding with the period when the prevalence of M. ovipneumoniae infection increased from 33% to 100% of the exposed lamb group. Others have also observed that the most dramatic effects of experimentally reproduced chronic non-progressive pneumonia occur during the first 30 days after challenge [5, 6]. Analysis of variance was conducted using the model ADG ~ Group + Sex + Birth type + error.…”
Section: Resultsmentioning
confidence: 99%
“…In severe cases, enzootic pneumonia may involve co-infection with multiple genetic strain types of M. ovipneumoniae and also other bacterial respiratory pathogens, including prominently Mannheimia haemolytica [3, 4]. Enzootic pneumonia has been associated with adverse effects on lamb growth and productivity [5-9].…”
Section: Introductionmentioning
confidence: 99%
“…They have found that, when over 20% of lung surface area had been affected by pneumonia, lamb bodyweight gain decreased from 136 to 65 g daily. In this sense, Alley (1987) have found a significant linear relationship between liveweight gain and the extent of the pneumonic lesions in experimentally infected lambs, which indicated that a reduction of nearly 1 kg/month could be expected for every 10% of the lung surface area affected. The same correlation was noted by Jones et al in 1982. In Spain, several surveys conducted in feedlots showed that lung lesions had also consequences in growth, feed conversion ratio and carcass quality (González et al, 2016) and specified an average loss of 36 g daily in affected Rasa Aragonesa lambs.…”
Section: Significance In Lambsmentioning
confidence: 90%
“…Chronic nonprogressive pneumonia is the most common form of ovine pneumonia in New Zealand, and is an important issue for sheep production, leading to reduced growth rate ( Kirton et al, 1976 ; Alley, 1987 ; Goodwin et al, 2004 ; McRae et al, 2016 ) and a predisposition to pleurisy ( Alley, 2002 ). There is well-documented evidence for between-animal variation in the ability of livestock to resist multiple diseases of economic importance, including respiratory disease ( Bishop and Morris, 2007 ; Davies et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%